Analytical Five-Phase Bus Rapid Transit Traffic Flow Model. Issue 1 (January 2015) - Hyland, Michael F.; Mahmassani, Hani S.
Bus rapid transit (BRT) systems are becoming increasingly popular in cities worldwide because of their ( a ) efficiency and reliability advantages over traditional bus service and ( b ) cost advantages over rail transit systems. As transportation decision makers consider the implementation and planning of BRT systems, it is important that they be able to analyze different operational components of these systems. This paper describes an analytical five-phase BRT traffic flow model that is able to model the movement of a bus throughout an entire BRT corridor and network. The five-phase model includes ( a ) a queuing model to determine the time a bus spends waiting for access to the loading area, ( b ) an access time model to determine the time that it takes a bus to access a loading area position from the queue when a loading position becomes available, ( c ) a nonlinear dwell time model to determine the time that a bus spends at a loading area position, and ( d and e ) a two-part model of the following behavior of buses between bus stations, dependent on whether there is a bus between the following bus and the approaching station. The five-phase BRT traffic flow model provides a comprehensive modeling framework for a networkwide simulation of a separate right-of-way BRT system. The model builds on research in the areas of car-following (and more recently bus-following) models, dwell time models, and bus station queuing models.